EFFECT OF DIFFERENT ANIMAL MATERIALS IN COMPOUNDED DIETS ON GROWTH, FEED CONVERSION EFFICIENCY AND BODY COMPOSITION OF MAJOR CARP CIRRHINUS MRIGALA - Rahman, Najib- Ur-; Mustafa, Saleem (Indian Journal of Fisheries, 2011)
Growth performance of major carp Cirrhinus mriga/a was evaluated in relation to six artificial diets ofdifferent chemical composition and energy value. Experimental data pointed that the diet-F (insect mealand linseed oil cake, 50:50) is the most effective dietary formulation. The high mutritional value of thisdiet was followed by other feeds: ’B’ (minced buffalo meat and linseed oil cake, 50:50); ’A’ (buffalo liverand linseed oil cake, 50:50); ’E’ (blood meal and linseed oil cake, 50:50); ’C’ (buffalo spleen and linseedoil cake, 50:50) and ’0’ (buffalo intestine and linseed oil cake, 50:50). Condition factor and biochemicalparameters maintained similar trend as a nutritional value in the specimens of various batches: F-B-AE-C-O